Problematika Eksepsi Dan Rekonvensi Dalam Praktek Peradilan Perdata - Anggi Sri Haryati Simarmata; Dzakki Risqullah Ismail; Rafael Roy Irawan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This article examines the doctrinal and procedural challenges in the application of exception (eksepsi) and counterclaim (rekonvensi) within Indonesian civil justice practice, emphasizing their normative structure and judicial interpretation. Using a normative juridical method with statutory and conceptual approaches, the study analyzes primary legal instruments including HIR, RBg, Burgerlijk Wetboek, and Rv, supported by jurisprudence and academic doctrine. The findings indicate that ambiguities in classification, procedural requirements, and the relational nexus between principal claims and counterclaims generate inconsistent judicial outcomes and weaken legal certainty. In addition, the lack of harmonization between traditional procedural norms and contemporary developments, such as electronic court systems and procedural justice principles, contributes to inefficiency and fragmentation in dispute resolution. The study proposes a systematic normative reconstruction through interpretative integration and regulatory refinement to enhance coherence and predictability. Strengthening the clarity and alignment of these procedural mechanisms is essential to ensuring an effective, fair, and modern civil procedural system in Indonesia.